Evaluation of the perception of universities’ role in the public procurement market - Kędra, Arleta (Ocena percepcji roli uniwersytetów na rynku zamówień publicznych, 2021)
The aim of the work is to examine how the role of universities in the public procurement market and in public-private partnership is perceived by both the contracting authorities and the contractors. It was verified whether the entities participating in public procurement and public-private partnership see the need for cooperation with universities, and whether there is a link between the declared need for cooperation and the assessment of real actions taken or provided by universities. The work is based on a survey conducted between March and May 2020 among 520 institutions representing contractors and procurers in public procurement. The highest evaluation was given to the activities of public universities in the field of public procurement and public-private partnership in Lubuskie and Śląskie (opinion of procurers) and Lubelskie and Warmińsko-Mazurskie (opinion of contractors). With the use of logistic regression models it was verified that there is a positive relation between the evaluation of the university’s activities and the declared need for cooperation between the university and the analysed entity.
Econometrics = Ekonometria, 2021, Vol. 25, No. 1, s. 82-90
Keywords: public procurement; public private partnership; university; zamówienia publiczne; uczelnie wyższe; partnerstwo publiczno-prywatne